Corneal Remodeling After Myopic SMILE Versus FS-LASIK: A Spatial Analysis of Short- and Mid-Term Corneal Thickness, Volume, and Shape Changes. Issue 7 (30th July 2022) - Lazaridis, Apostolos; Spiru, Bogdan; Giallouros, Elefterios; Droutsas, Konstantinos; Messerschmidt-Roth, Anke; Sekundo, Walter
Abstract : Purpose: To evaluate the short- and mid-term changes of corneal thickness spatial profile (CTSP), corneal volume distribution (CVD), and corneal asphericity after small-incision lenticule extraction (SMILE) for correction of myopia and astigmatism and compare the results with femtosecond laser–assisted laser in situ keratomileusis (FS-LASIK). Method: Thirty eyes of 18 patients who underwent SMILE were compared with a group of 30 eyes of 16 patients who underwent FS-LASIK. The groups were matched for preoperative central corneal thickness and lenticule thickness/ablation depth. Scheimpflug corneal tomography was performed preoperatively and postoperatively at 2 months and 3 years. The CTSP was evaluated on 4 concentric rings (2, 4, 6, and 8 mm). The CVD was evaluated at 3 concentric zones (3, 5, and 7 mm). Changes in the anterior and posterior asphericity at a 6-mm zone were also evaluated. Results: Between the 2-month and 3-year examination, the CTSP showed a similar increase for both groups at all measured points and rings ( P ≥ 0.168). The CVD also showed a similar increase for both groups at all measured zones ( P ≥ 0.278). The anterior corneal asphericity remained stable after SMILE (2-mo Q = 0.46 ± 0.27; 3-yr Q = 0.45 ± 0.27; P = 0.711) but decreased significantly after FS-LASIK (2-mo Q = 0.52 ± 0.47; 3-yr Q = 0.47 ± 0.44; P = 0.028). Similarly, the posterior corneal asphericity remained stable after SMILE (2-mo Q = −0.11 ± 0.15; 3-yr Q = −0.11 ± 0.13; P = 0.902) but decreased significantly after FS-LASIK (2-mo Q = −0.13 ± 0.14; 3-yr Q = −0.16 ± 0.15; P = 0.034). Conclusions: CTSP and CVD between the 2-month and 3-year examination showed a similar increase after SMILE and FS-LASIK. During the postoperative course, the anterior and posterior corneal asphericity remained more stable after SMILE compared with FS-LASIK.